Avaliação do uso do software educacional Gcompris: uma abordagem da interação humano-computador para o ensino e aprendizagem da matemática no ensino fundamental em uma escola pública de Castanhal/PA - SILVA, Marcela Teixeira da (2019)
The digital tools have become a great ally in the process of teaching and learning, especially in the disciplines that demand knowledge in mathematics. Thus, projects that aim to encourage the use of technologies to support digital inclusion are being used in public schools in our country. This is the case of Linux Educacional, promoted by the Ministry of Education (MEC), as a way of minimizing social exclusion and guaranteeing access to information and other technological benefits. From the theoretical subsidies of Abreu (2010), Canny (2006), Gladcheff (2001), Nielsen (2012), Vigotsky (1987), among others, we aim to develop this academic research, in order to analyze the transformations resulting from technological development in the areas of information and communication in society; possibilities and challenges of an education accompanied by technologies; Human-Computer Interaction (HCI) to enhance the relationship of users and educational technologies. To do so, through a quantiqualitative approach, we appropriate data collection instruments such as systematic observation and questionnaires. Thus, we carried out a case study in a municipal school in the municipality of Castanhal - Pará, located 64 km from the capital of Para, contrasting traditional educational processes with activities developed through the educational tool GCompris. In this sense, this research was able to present a teaching reading favorable to educational software, as well as to reveal about the positive differential of performance of learners who had moments of learning through educational technologies.